2011
DOI: 10.1021/ja200012e
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Silver Chalcogenide (Ag2E; E = Se, S, Te) Semiconductor Nanocrystals

Abstract: A general, one-pot, single-step method for producing colloidal silver chalcogenide (Ag(2)E; E = Se, S, Te) nanocrystals is presented, with an emphasis on Ag(2)Se. The method avoids exotic chemicals, high temperatures, and high pressures and requires only a few minutes of reaction time. While Ag(2)S and Ag(2)Te are formed in their low-temperature monoclinic phases, Ag(2)Se is obtained in a metastable tetragonal phase not observed in the bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
162
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(175 citation statements)
references
References 31 publications
11
162
0
Order By: Relevance
“…S1, ESI †) due to the reduced effects of the larger, whereas surface defects derived from the cation exchange were introduced to the smaller QDs, inducing a lower luminescence efficiency (QY) and even PL quenching, which is consistent with recent reports referring to CdTe and Ag 2 Te QDs. 21 For these QDs from the cation exchange, the highest QY (2.3%) was obtained for Ag 2 S QDs (D 2 ) prepared from CdS QDs (D 1 ). Previous studies have reported the relatively low QYs of Ag 2 S QDs, which may be from the inherent properties of Ag-based semiconductor NCs (QDs).…”
Section: Preparation and Characterization Of Cds And Ag 2 S Qdsmentioning
confidence: 95%
See 1 more Smart Citation
“…S1, ESI †) due to the reduced effects of the larger, whereas surface defects derived from the cation exchange were introduced to the smaller QDs, inducing a lower luminescence efficiency (QY) and even PL quenching, which is consistent with recent reports referring to CdTe and Ag 2 Te QDs. 21 For these QDs from the cation exchange, the highest QY (2.3%) was obtained for Ag 2 S QDs (D 2 ) prepared from CdS QDs (D 1 ). Previous studies have reported the relatively low QYs of Ag 2 S QDs, which may be from the inherent properties of Ag-based semiconductor NCs (QDs).…”
Section: Preparation and Characterization Of Cds And Ag 2 S Qdsmentioning
confidence: 95%
“…[17][18][19] Upon the phase transfer from organic solvent to water, the PL intensity and stability of Ag-based QDs probably are compromised drastically. 21,22 Therefore, the development of a simple and efficient synthetic method to prepare stable and water-dispersible NIR Ag 2 S QDs is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…2(e). The diffraction peaks could be indexed to the tetragonal phase of α-Ag 2 Se, 23 the data for which are not available in the database so far. The SAED pattern of the nanowires in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is exactly the region, in which Ag 2 Se shows its most intense Bragg peaks [31]. From these data it can be concluded that Ag 2 Se was formed during the XRD measurements as a product of the photodegradation of CdSe–Ag NPs through the X-ray irradiation.…”
Section: Resultsmentioning
confidence: 71%
“…According to previous investigations, CdSe nanocrystals that were exposed to Ag cations in solution could be completely or partially converted to Ag 2 Se via cation exchange [24]. Also, the possibility of Ag 2 Se formation from Ag + and TOPSe solutions at 125–185 °C was shown [3132]. The authors of [32] synthesized NPs with an exciton-PL maximum at ca.…”
Section: Resultsmentioning
confidence: 99%